2017
DOI: 10.1161/jaha.116.004809
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Fibrosis Is Universal Following Fontan Operation, and Severity is Associated With Time From Surgery: A Liver Biopsy and Hemodynamic Study

Abstract: BackgroundCongestive hepatopathy is a recognized complication of Fontan physiology. Data regarding the incidence of hepatopathy and risk factors are lacking.Methods and ResultsLiver biopsies and cardiac catherizations were performed as part of an evaluation offered to all patients ≥10 years after Fontan. Quantitative determination of hepatic fibrosis was performed using Sirius red staining with automated calculation of collagen deposition per slide (%CD). Biopsies from included subjects were compared to staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(203 citation statements)
references
References 34 publications
5
197
1
Order By: Relevance
“…It is known that Fontan configuration results in central venous congestion and reduced cardiac output. Some of the complications, such as PLE and hepatic dysfunction have been associated with the abnormal physiology offered by the Fontan circuit 27. Therefore, some argue that delaying the Fontan operation may help with postponing the onset of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Fontan configuration results in central venous congestion and reduced cardiac output. Some of the complications, such as PLE and hepatic dysfunction have been associated with the abnormal physiology offered by the Fontan circuit 27. Therefore, some argue that delaying the Fontan operation may help with postponing the onset of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that time after the Fontan procedure was the only factor significantly associated with collagen deposition, which suggested that liver fibrosis was an inherent feature of Fontan physiology. 20 However, no inflammation or hepatocellular damage was evident in patients undergoing the Fontan procedure, suggesting that fibrosis may be mediated by a non-inflammatory mechanism. 21 We could not determine the most reliable marker for the detection of liver disease in patients undergoing the Fontan procedure in the present study.…”
Section: Advance Publication By-j-stagementioning
confidence: 98%
“…Post-operatively six patients were extubated at a median of 3 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and the other three required tracheostomy at a median of 17 days (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Post-operatively six patients were extubated at a median of 3 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and the other three required tracheostomy at a median of 17 days (14)(15)…”
Section: Peri-operativementioning
confidence: 99%
“…1 Fontan failure occurs due to systolic or diastolic dysfunction, atrioventricular valve regurgitation, arrhythmia, and/or lymphatic abnormalities. 4 Orthotopic heart transplantation (OHT) is a valuable treatment for Fontan failure. The pathophysiology of liver injury likely starts in utero and includes ischemia and tissue hypoxia associated with staged surgical palliation and the increased central venous pressure from total cavopulmonary anastomosis.…”
Section: Introductionmentioning
confidence: 99%